2021
DOI: 10.1364/ol.414926
|View full text |Cite
|
Sign up to set email alerts
|

10  J operation of a conductive-cooled Yb:YAG active-mirror amplifier and prospects for 100  Hz operation

Abstract: We report, to the best of our knowledge, the highest power conductive-cooled active-mirror amplifier (CcAMA) using Yb:YAG with a pulse energy of 10 J. By using four liquid-nitrogen circulating cooled laser heads, we achieved a repetition rate, pulse energy, and average power of 33.3 Hz, 9.3 J, and 310 W, respectively. The problem of wavefront distortion, which is difficult to solve with a large-aperture active-mirror laser, is suppressed by using reinforcing materials with the same thermal expansion coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…[111,149,150] Based on the cryogenically cooled Yb:YAG active mirrors and pulsed diode laser pumping, Wang et al reported a laser pulse output of 1 kHz, 4.5 ps, 1.1 J, which is the highest average power Joule-level ps laser reported at that time. [64] Based on four liquid nitrogen circulating cooled laser heads, [49] Ogino et al achieved a laser output of 9.3 J, 10 ns, at 33.3 Hz.…”
Section: Gas and Cryogenic Coolingmentioning
confidence: 99%
See 3 more Smart Citations
“…[111,149,150] Based on the cryogenically cooled Yb:YAG active mirrors and pulsed diode laser pumping, Wang et al reported a laser pulse output of 1 kHz, 4.5 ps, 1.1 J, which is the highest average power Joule-level ps laser reported at that time. [64] Based on four liquid nitrogen circulating cooled laser heads, [49] Ogino et al achieved a laser output of 9.3 J, 10 ns, at 33.3 Hz.…”
Section: Gas and Cryogenic Coolingmentioning
confidence: 99%
“…The master amplifier consisted of four large‐aperture Yb:YAG ceramics (a diameter of 60 mm and thickness of 7 mm), liquid nitrogen cooled at 78 K, and PDL pumped. [ 49 ] They aimed to scale the energy to 100 J with 10 GW peak power by combining more than 10 large‐aperture laser heads. However, there is still no public report of more than 10 GW peak power by the active mirror.…”
Section: Solid‐state Lasers With High‐peak‐powermentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, an e cient ampli er is required, but which must keep the ST correlation unchanged. Because of low gain (e.g., ~3× per 7mm in a conductive-cooled Yb:YAG [29]), the population inversion ampli er containing energy-level laser media requires a long-length propagation and/or a multiple-pass con guration for high energy ampli cation, which is not suitable here. OPA based on the three-wave coupling in nonlinear crystals can realize high gain within a thin crystal (e.g., 20× per 0.5mm in a 40 fs typeI-BBO OPA [30] and 10 6 × per 15mm in a 3 ps typeI-BBO OPA [31]), which might be an ideal ampli er for ST wave packets.…”
Section: Introductionmentioning
confidence: 99%